Meningkatkan Keterampilan Mengajar Guru Bidang Studi Agama Melalui Pembimbingan Dan Praktek Mengajar - Alhafif Syahputra (Pusdikra Publishing, 2021)
Teachers in the field of Religious Studies have poor teaching skills. Teachers are always given instruction in the traditional lecture format, which is not accompanied by any teaching techniques. Through mentoring and teaching methods, this project intends to strengthen the teaching skills of Religious Studies teachers at MTsN Pematangsiantar. This research uses a school action research approach, research was undertaken at MTsN Pematangsiantar with a total of 15 teachers involved, and it is a school action research project. The findings revealed that 1) the mean value of teacher teaching skills increased significantly, 2) the mean value of teacher teaching skills in Pre-cycle was 112,00, and the mean value of teacher teaching skills in Cycle I increased to 220,47, and 3) the mean value of teacher teaching skills in Cycle II increased to 253,40.